R. K. Narayan’s Philosophy of Life: A Study of Selected Short Stories in Malgudi Days: Exploring R.K. Narayan's Vision of Life in Malgudi Days (Journal of Advances and Scholarly Researches in Allied Education, 2018)
R.K. Narayan enjoyed wide popularity not only in India but abroad also particularly in England and U.S.A. In America he is regarded next to Faulkner. He was also included in Writers and Their Works published by The British Council - only Indian to achieve this distinction. Many of his short stories were broadcasted by B.B.C. - a rare distinction. Both University of Leeds and Delhi University honored him with the degree of D. Litt. Moreover he won Sahitya Akademi Award for his novel The Guide (1958) in 1960 and The Indian Government awarded him with Padma Bhushan in 1964 for his achievements. The sole aim of his all writings is to give aesthetic satisfaction. He never considers art as a medium of propaganda as in case of Mulk Raj Anand. He interprets Indian life purely for ‘the art for readers’. As a result, the incongruous and the absurd in life does not annoy him, it only amuses him. This has been the characteristic stance of humorists from Chaucer to Modern times. His success as a writer lies in his ability to communicate this spirit of amusement and delight in life to the reader. Narayan is actually a gentle novelist and short story writer who deeply loves his country and his countrymen. His criticism, even when it is bitter and far- reaching, can never be violent and what one gets in his novels perfectly illustrates the gentleness and humanity of his country. As a humanist, Narayan could not possibly accept the dichotomy of town and country. Men are the same everywhere, each born with his own qualities, be they good or bad, and each only fractionally moulded by his environment. Everything is to be found in Narayan’s villages - good, evil and murders. Officials are corrupt and inefficient. Narayan masters sufficiently the art of novel writing not to make an in-depth study of corruption. He merely sprinkles his remarks here and there and his casual approach gives them strength as it makes corruption seem a perfectly normal part of life.